Performance and Cost Analysis of Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry for Routine Identification of Yeast - Dhiman, Neelam (American Society for Microbiology, 2011)
Matrix-assisted laser desorption ionization–time of flight (MALDI-TOF) mass spectrometry was compared to phenotypic testing for yeast identification. MALDI-TOF mass spectrometry yielded 96.3% and 84.5% accurate species level identifications (spectral scores, ≥1.8) for 138 common and 103 archived strains of yeast. MALDI-TOF mass spectrometry is accurate, rapid (5.1 min of hands-on time/identification), and cost-effective ($0.50/sample) for yeast identification in the clinical laboratory.